Blood Bank Service: An Experience at Newly Established Birat Medical College and Teaching Hospital, Tankisinuwari, Morang, Nepal - Kafle, Santosh Upadhyaya; Jha, K K; Sigh, M; Rana, R (Birat Journal of Health Sciences, 2017)
Introduction Blood bank service facility of blood collection, storage and dispatching began from 19 June 2016 in the new blood bank and transfusion service unit, at Birat Medical College & Teaching Hospital, Tankisinuwari, Morang, Nepal, with the support of Nepal Red Cross Society. As the supply of blood is finite, the inappropriate use of blood transfusion units and its component in the world exist, hence there is a need to monitor and regulate these services. Objectives The objective of this study is to know and identify different blood groups and its utilization pattern to meet the demand for future preparedness and to identify the total blood unit, which are being, replaced back. Methodology This retrospective study was conducted at BMCTH, Tankisinuwari, Morang for component dispatches from 19th June, 2016 to 19th February, 2017. Requisitions for whole blood requirement for patients from various departments were reviewed regarding the department request, the whole blood requested and whether being replaced, blood group and socio-demographic profile. Results Out of 193 transfusion units dispatched, 28 patients were male and 165 patients were females respectively B positive blood groups were most common, followed by A positive, O positive, AB positive, both AB and O negate respectively. The largest numbers of requisitions were from Gynecology and Obstetrics ward in the hospital, while 22 requisites were from other health centers. Majority of the requisitions were for 51- 60 years age group from the local district Morang. The total number of blood units replaced were 38, out of which 5 for males and 33 for females respectively. Conclusion B positive was the predominant requested blood group, with Gynecology and Obstetrics ward demanding the most requests, among 51-60 years age group from Morang district. The total blood units being replaced were very less in number with some requisition forms, which lacked essential details. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 98-101